RISK ANALYSIS AND INTERNAL CONTROL ASSESSMENT - PREMISES FOR IMPROVING MANAGEMENT AT THE LEVEL OF ROMANIAN PUBLIC ENTITIES - CRISTINA MARIA VOINEA; VIOLETA STATE (Annals of the University of Petrosani: Economics)
Romania, as a European Union member state, has undergone, in recent years, a complex process of reform in all activity fields. This includes the current process of public administration reform, which aims to improve the management, the administrative capacity and the manner in which the entire Romanian public sector is organized. In this study, we intend to portray the manner in which the internal control system and the internal audit structure of a Romanian public entity are shaped into form. For exemplification, we chose the internal audit mission titled “The Accounting System and Its Reliability”. We will identify the risks, we will assess them and we will also propose measures through which the entity’s management may mitigate these risks by correcting registered deviations.